2016
DOI: 10.3177/jnsv.62.249
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Green Tea Extract and Eriodictyol Inhibited High-Fat/High-Sucrose Diet-Induced Cholesterol Upregulation Is Accompanied by Suppression of Cholesterol Synthesis Enzymes

Abstract: Summary Western diets induce obesity associated with an increased risk of hypercholesterolaemia. Indeed, obesity-induced hypercholesterolaemia is correlated with increased coronary cardiovascular disease (CVD) risk. Male C57BL/6J mice were fed a normal diet, highfat and high-sucrose diet (HF/HS), HF/HS with green tea extract powder diet (HF/HS1GT), HF/HS with eriodictyol diet (HF/HS1Eri), or HF/HS with green tea extract powder and eriodictyol diet (HF/HS1GT1Eri) for 8 wk. Body weight was lower in the HF/HS1GT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Combination therapy with catechins and caffeine markedly reduced intracellular fat accumulation by regulating the gene and protein expression levels of lipid metabolism-related enzymes. Yamashita et al [76] found that, following supplementation with green tea extract powder and eriodictyol for 8 weeks, body weight, food intake, cholesterol levels, and LDL levels were decreased, accompanied by the suppression of two kinds of cholesterol synthesis enzymes, 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), and 3-hydroxy-3-methylglutaryl-coenzyme A synthase (HMGCS).…”
Section: Resultsmentioning
confidence: 99%
“…Combination therapy with catechins and caffeine markedly reduced intracellular fat accumulation by regulating the gene and protein expression levels of lipid metabolism-related enzymes. Yamashita et al [76] found that, following supplementation with green tea extract powder and eriodictyol for 8 weeks, body weight, food intake, cholesterol levels, and LDL levels were decreased, accompanied by the suppression of two kinds of cholesterol synthesis enzymes, 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), and 3-hydroxy-3-methylglutaryl-coenzyme A synthase (HMGCS).…”
Section: Resultsmentioning
confidence: 99%
“…Until now, EDT has attracted more interesting as a therapeutic agent in many diseases, such as hypercholesterolemia, cerebral ischemia, cardiovascular diseases and neurodegenerative diseases ( Jing et al, 2015 ; Lee et al, 2015 ; Ferreira Ede et al, 2016 ; Yamashita et al, 2016 ). In the present study, we utilized an ex vivo model to explore the protective effect of EDT against myocardial I/R-induced cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…This result shows that the western diet used was efficient to promote obesity in the experimental period of 20 weeks. According to the literature, western diet/ hypercaloric diets are associated with higher body weight in rodents [ 12 , 18 , 26 , 27 ]. Besides, the HSF animals in this study also presented many disorders similar to human obesity-related comorbidities, such as hypertension, dyslipidemia hypertriglyceridemia, glucose intolerance, insulin resistance, and hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%